Harmonisasi dan keselarasan hidup dalam cerpen Harta Gantungan karya Ahmad Tohari - Khasanah, Venus; Prakoso, Teguh (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Kang Nurya's persistence in preserving buffalo as the hanged treasure is the center of the story discussed in the "Harta Gantungan" storiette. Although the neck swelling could take his life, Kang Nurya believes that death is a human cycle and chooses not to seek medical treatment. Kang Nurya believes that the consequences of medical expenses will have implications for the sale of his favorite buffalo, which is actually prepared for the cost of taking care of his body later. A discussion about this then took place with Markotob, who also believes that death is a destiny that must be faced. However, the way to prepare for it is not like Kang Nurya's thinking. The dialog between the two brings out the balance of views on the concept of death. The purpose of this research is to find the balance through harmonization and harmony of life based on the author's worldview. The theory used is Lucien Goldmann's genetic structuralism and Mukařovský's literary aesthetics with a literary sociology approach. The research result shows that there is a harmonization and live conformity that appear on that storiette, and that is the world view of Ahmad Tohari. Internal conflict in Kang Nurya is moderated by Markotob, showing the discussion about the meaning of death. Both have the same view about death but with different thinking methods. Even though Kang Nurya is stubborn, Markotob still respects him. Moreover, in the end, Kang Nurya did not know that his death did not use the hanged treasure that he had taken care of at all.